A One-Two Punch: Hydralazine-Induced Liver Injury in a Recovering Ischemic Hepatitis. (July 2016) - Alansari, Ahmed; Quiel, Luis; Boma, Noella
Abstract : A 77-year-old woman presented to the emergency department with a 2-day history of nausea and vomiting. Her medical history included diabetes mellitus, hypertension, atrial fibrillation, dilated cardiomyopathy, and coronary artery disease. Her home medications included aspirin, clopidogrel, warfarin, digoxin, metoprolol, losartan, simvastatin, isosorbide dinitrate, furosemide, and spironolactone. Initial physical examination showed blood pressure of 170/80 mm Hg with a heart rate of 69 beats per minute, otherwise unremarkable. Initial laboratory workup was significant for INR of 3.6, with slightly elevated troponin I and creatinine of 0.06 ng/mL and 1.4 mg/dL, respectively. The patient was admitted to the medicine floor. However, a few hours later, her atrial fibrillation went into rapid ventricular response, associated with hypotension. Cardiac enzymes began to trend up along with worsening of her renal function tests and hepatic enzymes. Her INR remained supratherapeutic despite holding coumadin and giving vitamin K. The patient was transferred to the medical intensive care unit for closer monitoring. During day 1 of the medical intensive care unit stay, losartan, simvastatin, and diuretics were held, whereas aspirin, clopidogrel, and isosorbide dinitrate were continued. In the following 2 days, there was worsening of tissue perfusion, and laboratory workup showed AST 514 IU/L, ALT 391 IU/L, INR >9, creatinine 3.8 mg/dL, and troponin I 0.19 ng/mL; therefore, digoxin was also held. Once the patient achieved hemodynamic stability, she was started on hydralazine. On day 4, renal function, cardiac, and hepatic enzymes improved significantly. However, 24 hours later, transaminases began to trend up again reaching a maximum of AST and ALT of 359 and 525 IU/L, respectively. Other possible causes were ruled out because her viral hepatitis markers, antihistone antibody, antinuclear antibody, and anti–double-stranded DNA were all negative. After thorough review of all medications, hydralazine was held with subsequent improvement in transaminases. The patient was seen a month later after her discharge, and all her laboratory workup improved to baseline.